El condicionamiento de fonemas y su interpretación - Fernandez, Gustavo; Natalicio, Luiz F.S.; Natalicio, Diana S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Conditioning o f the phoneme /v/ was attempted in 5 Ss. Only one S solved the problem; i.e., derived the rule, eliminating all hypotheses except the relevant one. Results are interpreted in terms of problem solving behavior, hypothesis testing behavior, and in the light of the most recent theoretical approximation to the experimental analysis of behavior.